The Effect of Addition EM4 Solution on Vermicomposting Fish Waste to Increase CNPK Regosol Soil - Vivin Setiani; Tanti Utami Dewi; Ayu Nindyapuspa; Dinda Maya Kristina; Yesica Novrita Devi (Universitas Diponegoro, 2023)
The Environmental Service Surabaya noted that waste generation at Benowo Landfill reached 1,600 tons/day. 60% of waste generation at Benowo Landfill was dominated by organic waste. One of organic waste was fish waste, vegetable waste, and some waste from household business activities such as sawdust. One of method composting to reduce organic waste is vermicomposting. Lumbricus rubellus is a type of worm that eats leaf litter so, it is suitable to be used decompose organic waste. The adding of EM4 solution can make more fast of composting process. The compost could be applied in regosol soil to improve soil CNPK quality. The purpose of this study was to analyze the effect of EM4 variations on the quality of compost based on SNI 19-7030-2004 and the effect of adding the compost to regosol soil. The research result showed that the quality of compost complies with SNI 19-7030-2004. The statistical analysis showed that EM4 has a significantly effect on compost quality and regosol soil improvement.